Layout and cross-sectional size optimization of truss structures with mixed design variables based on gradient method - Peleshko, Ivan; Yurchenko, Vitalina; Rusyn, Pavlo (Eastern-European journal of enterprise technologies, 2023)
The object of the study was truss-type rod structures, which were investigated for the purpose of finding the optimal design solution in a mixed (continuous and discrete) space of variables. The parameters of the geometric scheme of the truss, as well as the dimensions of the cross-sections of its elements, were considered as design variables. The stated optimization problem is represented as a nonlinear programming task, in which the objective function and nonlinear constraints of the mathematical model are continuously differentiable functions of the design variables. The system of constraints includes strength and stability inequalities, formulated for the design cross-sections of the rod elements of the structure, which is subject to the effect of the design load combinations of the ultimate limit states. As a part of the system of constraints, the displacement constraints formulated for the specified structural nodes, which is subject to the action of design load combinations of the serviceability limit states, are considered. To solve the stated optimization problem, a method of the objective function gradient on the surface of active constraints was used, with the simultaneous elimination of residuals in the violated restrictions. For design variables, the variation of which must be performed according to a given set of possible discrete values, a discretization procedure for the optimal solution obtained in the continuous space of design variables is proposed. A comparison of the proposed optimization methodology with alternative metaheuristic methods and algorithms reported in the literature was performed. On the considered problem of parametric optimization of a 47-span tower structure, a design solution with a weight of 835,403 kg was obtained, which is 1.53...4.6 % better than the optimal solutions obtained by other authors Об’єктом дослідження виступали стержневі конструкції типу ферм, які досліджувались на предмет пошуку оптимального проектного рішення у змішаному (неперервному та дискретному) просторі змінних. В якості змінних проєктування розглядались параметри геометричної схеми ферми, а також розміри поперечних перерізів її елементів. Сформульована задача оптимізації представлена як задача нелінійного програмування, в якій функція мети та нелінійні обмеження математичної моделі є неперервно диференційованими функціями змінних проєктування. До системи обмежень залучені обмеження міцності та стійкості, сформульовані для розрахункових перерізів стержневих елементів конструкції, що підлягає дії розрахункових комбінацій навантажень першої групи граничних станів. У складі системи обмежень розглянуті обмеження переміщень, сформульовані для визначених вузлів конструкції, що підлягає дії розрахункових комбінацій навантажень другої групи граничних станів. Для розв’язку сформульованої задачі оптимізації використовувався метод градієнту функції мети на поверхню активних обмежень з одночасною ліквідацією нев’язок у порушених обмеженнях. Для змінних проєктування, варіація яких повинна виконуватись відповідно до заданої множини можливих значень, запропонована методика дискретизації оптимального рішення, отриманого у неперервному просторі змінних проєктування. Виконане порівняння запропонованої оптимізаційної методології з альтернативними представленими в літературі метаеврістичними методами та алгоритмами. На розглянутій задачі параметричної оптимізації 47-мистержневої конструкції башти отримане проектне рішення масою 835.403 кг, що на 1,53…4,6 % є кращим за оптимальні рішення, отримані іншими авторами